If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying F(2) = 12 * 2 + -6 Reorder the terms for easier multiplication: 2F = 12 * 2 + -6 Multiply 12 * 2 2F = 24 + -6 Combine like terms: 24 + -6 = 18 2F = 18 Solving 2F = 18 Solving for variable 'F'. Move all terms containing F to the left, all other terms to the right. Divide each side by '2'. F = 9 Simplifying F = 9
| 3x+12-x=18 | | 16*11+7x*16=2640 | | 16*11+7x=2640 | | 19x-162=9 | | 9(20x-19)=2169 | | 3*4x-3*3=12x-2 | | 14(6+17x)=3654 | | 15x-38=7 | | 22x-410=8 | | 10*4x-3*10=38-6 | | 4x^2-10x-1=0 | | 19*5-8x*19=-2185 | | 17x-222=16 | | 17x=323 | | 15(5-14x)=-2655 | | 11*9-8*9=97-2 | | 3*4+21x*6=1272 | | 16(17x-21)=2656 | | 12x=264 | | 5*10x-3*5=48x-3 | | (p-7)/4=(2p/3)+2 | | 18(3+18x)=3942 | | 3*4+21x*3=1272 | | 3*4+21x=1272 | | 6*10x-5*6=58x-3 | | 4(6x-7)=22x-4 | | 9*12x-11=225 | | 18x-392=4 | | 1+3x-x^3=3x+3 | | 12(9x-3)=106x-4 | | 3y=-8-4 | | 11(4x-2)=42x-2 |